URGENSI PRESERVASI INFORMASI DALAM KONTEKS ARSIP KELUARGA - Mifta Olievia Wardhani (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
Various types of records must have a valuable system for managing and maintaining records. Generally management records activity are managed by records institution in the scale institution, regional, and national. There is one types of records that also needed better management process, that is family records. Family records is one type of arhives that is belong to personal archives or records, every person in the scope of that family must be responsible for taking care their records, this is also known as preserving family records. Preserving family records can be done in a simplest way, such as storing records document in a records shelf or storage box, paying attention in room condition for storing records, and also classified records by their types, its use, and year. The aim of preserving family records are to maintain the information inside that records, preventing records from destructive elements from human error and disaster. And importantly, making information or records retrieval process easier whenever needed in the future.